Investigating reduction and oxidation of La0.72Sr0.18Fe0.9Ni0.1O3–δ as a Co-free perovskite electrode for symmetrical solid oxide cells - Siavash M Alizadeh; Pascal Roussel; Mohammad Golmohammad; Valerie Theuns; Duncan Fagg; Oleg I Lebedev; Elise Berrier; Yury V Kolen’Ko (JPhys Energy)
Iron-based perovskites are of increasing interest for applications in symmetrical reversible solid oxide cells used for hydrogen production via steam electrolysis and power generation in a fuel cell configuration. We synthesize La _0.72 Sr _0.18 Fe _0.9 Ni _0.1 O _3– _δ as a potentially new candidate for this application, employing rapid nonequilibrium auto-combustion synthesis. Using powder x-ray diffraction and electron microscopy, we reveal that the material is an ABO _3 -type perovskite with an orthorhombic crystal structure. This compound exsolves small FeNi particles upon thermal treatment in a hydrogen-containing reductive atmosphere. These particles exhibit a cubic crystal structure with predominantly exposed [001] facets. The exsolution is assisted by the structural transformation of the parent orthorhombic ABO _3 -type perovskite into a Ruddlesden–Popper A _2 BO _4 -type perovskite with a tetragonal structure. Conveniently, the exsolution can be tailored to be either partially or completely reversible, depending on the temperature of the subsequent thermal treatment in an oxidative atmosphere. This correspondingly affords either the formation of a perovskite/nickel-ferrite spinel composite or reversion to the parent La _0.72 Sr _0.18 Fe _0.9 Ni _0.1 O _3– _δ perovskite. The newly synthesized Co-free La _0.72 Sr _0.18 Fe _0.9 Ni _0.1 O _3– _δ material is electrochemically investigated as an air electrode in a symmetrical solid oxide fuel cell, demonstrating good performance, with total polarization resistances of 2.42 and 0.33 Ω cm ^2 at intermediate (650 °C) and conventional (800 °C) operating temperatures, respectively. Finally, we show that the polarization resistance at the intermediate temperature is significantly reduced from 2.42 to 1.63 Ω cm ^2 through the observed formation of nickel-ferrite spinel upon redox cycling.